Follow-up of Patients with Low-risk Papillary Thyroid Carcinoma and Undetectable Basal Serum Thyroglobulin After Ablation Measured with a Sensitive Assay: A Prospective Study - Rosario, P. W. S.; dos Santos, J. B. N.; Calsolari, M. R. (Hormone and Metabolic Research, 2013)
The importance of thyroglobulin (Tg) stimulation after ablation in patients with papillary thyroid carcinoma (PTC) and undetectable basal Tg measured with sensitive assays has been questioned. However, there is a need for prospective studies that evaluate the evolution of these patients when stimulated Tg is omitted and this was the objective of the present investigation. One hundred twenty-two consecutive patients with PTC with the following characteristics were evaluated: submitted to total thyroidectomy and remnant ablation; low risk for recurrence; undetectable basal Tg (functional sensitivity of 0.1 ng/ml) 6 months after initial therapy; anti-Tg antibodies (TgAb) negative, and neck ultrasound (US) showing no abnormalities. These patients were not submitted to Tg stimulation. After follow-up for 24–78 months, only one patient (0.8%) presented apparent disease (lymph node metastases). TgAb were detected at low titers and without progression in 1 patient (0.8%). Tg became detectable and continued to be detectable in 3 patients (2.4%), but at concentrations ≤0.3 ng/ml in the absence of further increases, with stimulated Tg < 1.4 ng/ml. A total of 117 patients (96%) coursed with no apparent disease throughout follow-up and had undetectable Tg at the end of the study. Of these, 111 showed undetectable Tg in all measurements and 6 showed detectable Tg in some of them, although Tg later returned spontaneously to an undetectable range. After ablation, the risk of recurrence is very low in patients with low-risk PTC who show undetectable basal Tg measured with a sensitive assay, negative TgAb and negative US.
Keywords: low risk patients; sensitive thyroglobulin assay; thyroglobulin stimulation; long-term follow-up